2021
DOI: 10.1039/d0tc05071g
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic prediction on the configuration- and temperature-dependent dielectric constant of Be0.25Mg0.75O superlattice as a high-κdielectric layer

Abstract: Through DFT calculations, a Be0.25Mg0.75O superlattice having long apical Be–O bond length is proposed to have a high bandgap (>7.3 eV) and high dielectric constant (∼18) at room temperature and above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A recent ab initio calculation also supported this result, which indicated that maintaining a large bandgap value of >8 eV was possible. 34 Therefore, it could be anticipated that stacking the MgO and BeO layers was a feasible method to improve the electrical performances of the two constituting films while improving the electronic device stability over water-induced degradation. Nevertheless, as the Be compound is carcinogenic, it should be properly handled with adequate precaution.…”
Section: Introductionmentioning
confidence: 99%
“…A recent ab initio calculation also supported this result, which indicated that maintaining a large bandgap value of >8 eV was possible. 34 Therefore, it could be anticipated that stacking the MgO and BeO layers was a feasible method to improve the electrical performances of the two constituting films while improving the electronic device stability over water-induced degradation. Nevertheless, as the Be compound is carcinogenic, it should be properly handled with adequate precaution.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for that is that the “overbinding” LDA (prior research) relates to an artificially “strained” structure if compared to the “underbinding” GGA (PBEsol in our case), so imaginary GGA frequencies turn into positive LDA frequencies. Since the dielectric constant goes with the inverted squared frequencies, the numerical differences are rather large, despite very similar electronic structures, well known and discussed before 3,5 …”
Section: Resultsmentioning
confidence: 79%
“…Since the dielectric constant goes with the inverted squared frequencies, the numerical differences are rather large, despite very similar electronic structures, well known and discussed before. 3,5 As soon as external tensile strain is applied; however, there is huge boost of dielectric permittivity, particularly at low temperature, arising from the softening of the TO mode as shown in Figure 3 D. The strain sensitivity also indicates that it is possible to engineer dielectric permittivity through epitaxial strain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations